People’s perception on urban traffic congestion; a case study on Chittagong Metropolitan City, Bangladesh - Al-Qadery, Shahek MMA; Muhibbullah, Md (Chittagong University Journal of Biological Sciences, 2013)
An attempt has been taken to identify the major causes of traffic congestion along with existing system deficiencies, their consequences, and finally a policy options are recommended on Chittagong Metropolitan City. For the study primary data were collected through questionnaire survey and secondary data were used from various sources. The collected data were analyzed by using statistical techniques. It was found that rapid growth of population, inefficient land use pattern, indiscriminate roadside uses, past urban development trends and inadequate land use planning are responsible for traffic congestion in the city area. Lack of coordination and integration of concerned institutions is one of the major system deficiencies of traffic congestion situation in the study area. Opinion survey revealed that the overall quality of transportation system of Chittagong city is unsatisfactory. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13415 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):149-160, 2008